Design and kinematic of a dexterous bioinspired elephant trunk robot with variable diameter. (1st July 2022) - Zhou, Pan; Yao, Jiantao; Wei, Chunjie; Zhang, Shuai; Zhang, Hongyu; Qi, Shupeng
Abstract: How to further improve the dexterity of continuum robots so that they can quickly change their structural size like flexible biological organs is a key challenge in the field of robotics. To tackle this dexterity challenge, this paper proposes a soft-rigid coupled bioinspired elephant trunk robot with variable diameter, which is enabled by combining a soft motion mechanism with a novel rigid variable-diameter mechanism (double pyramid deployable mechanism). The integration of these two mechanisms has produced three significant beneficial effects: (i) The coexistence of multi-degree-of-freedom motion capability and variable size function greatly improves the dexterity of the elephant trunk robot. (ii) The motion refinement can be improved by structural amplification, making up for the low resolution of soft actuators. (iii) Its stiffness can be increased by enlarging its diameter, while its reachable workspace can be increased by decreasing its diameter. Thus, the elephant trunk robot can optimize its performance when facing different tasks by opening and closing the rigid variable-diameter mechanism. Further, we established a kinematic model of the elephant trunk robot by the structure discretization method and the principle of mechanism equivalence, and experimentally verified its reasonableness. The demonstration experiments show that the elephant trunk robot has good flexibility. This work provides a new variable diameter configuration for continuum robots, and presents a method of how to analyze the kinematics of continuum mechanisms using rigid mechanism theory.